2007
DOI: 10.1261/rna.546207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target secondary structure on RNAi efficiency

Abstract: RNA interference (RNAi) mediated by small interfering RNAs (siRNAs) or short hairpin RNAs (shRNAs) has become a powerful tool for gene knockdown studies. However, the levels of knockdown vary greatly. Here, we examine the effect of target disruption energy, a novel measure of target accessibility, along with other parameters that may affect RNAi efficiency. Based on target secondary structures predicted by the Sfold program, the target disruption energy represents the free energy cost for local alteration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 57 publications
6
130
0
2
Order By: Relevance
“…S2B). As presented elsewhere (27), we have also found that the activity in the cDNA dataset was significantly correlated with target disruption energy, a measure of accessibility of the target mRNA. cDNA-derived shRNAs showed lower activity when their disruption energy was <−15 kcal/mol, which we have used as the sixth filtering criterion.…”
supporting
confidence: 77%
“…S2B). As presented elsewhere (27), we have also found that the activity in the cDNA dataset was significantly correlated with target disruption energy, a measure of accessibility of the target mRNA. cDNA-derived shRNAs showed lower activity when their disruption energy was <−15 kcal/mol, which we have used as the sixth filtering criterion.…”
supporting
confidence: 77%
“…Known factors that influence siRNA efficacy include the difference in the duplex end thermodynamic stabilities (DDG) (Khvorova et al 2003;Schwarz et al 2003), sequence motifs within the guide strand (Reynolds et al 2004;Saetrom and Snove 2004), the overall duplex stability (Reynolds et al 2004), and the target site accessibility (Heale et al 2005;Shao et al 2007). Of these, only the strand's sequence similarity to highly effective standard siRNAs and DDG showed weak to strong correlations with the observed siRNA activities.…”
Section: Resultsmentioning
confidence: 99%
“…We used RNAfold (Hofacker 2003), RNAhybrid (Rehmsmeier et al 2004), and sfold (Shao et al 2007) to compute duplex end and intrastrand stability, overall duplex stability, and target site accessibility. To compute the stability of a given duplex end without overhangs, we placed 1-5 nt from each strand on opposite ends of an artificial hairpin sequence cassette (59-CCLLLL LGG-39; L denotes a loop nucleotide) and used RNAfold to predict the stability of the resulting hairpin sequence.…”
Section: Calculating Thermodynamic Featuresmentioning
confidence: 99%
“…When searching for factors influencing knock-down efficiency, attention turned to the local RNA structure at siRNA target sites and it was demonstrated that local RNA target structure is an important factor for siRNA efficacy (Schubert et al, 2005). Accordingly, siRNA design tools started to accommodate not only properties of siRNAs but also properties of the target site because it strongly increased efficiency of designed siRNAs (Heale et al, , 2006Shao et al, 2007;Tafer et al, 2008).…”
Section: Binding Site Accessibilitymentioning
confidence: 99%